STUDENTS’ PERCEPTION OF EDUCATIONAL PODCAST TO ENHANCE THEIR LISTENING SKILLS - Ikrar, Muh. Qusay; Fauzan, Muhammad Miftah; Sakkir, Geminastiti (Universitas Negeri Makassar, 2024)
This study aims to determine the perceptions of English Education students towards educational podcasts as a tool to improve their listening skills. The subjects of this study were five students of English Education class E. The interview was used as the main instrument to collect data. The results of this study show that three English education students perceive that they use podcasts quite often to improve their listening skills. There are several reasons, namely podcasts have flexibility in viewing time, can increase student learning motivation, and also podcasts can increase student vocabulary. The other two perceive that they do not often use podcasts to improve their listening skill because there are several reasons, such as the videos they watch are sometimes too long and also the influence of networks that are sometimes less supportive so that they interfere with students' focus on watching podcasts.